Fracionamento de cobre em sete solos do Estado do Ceará. - Romero, Ricardo Espíndola (1994)
In seven soil of Ceará State, Brazil, classified as "Areia Quartzosa distrófica" (AQd), "Aluvial eutrófico" (Ae), "Bruno não Cálcico" (NC), "Cambissolo eutrófico" (Ce), "Podzólico Vermelho Amarelo" (PV), "Podzólico Vermelho Amarelo eutrófico" (PE), Latossolo Vermelho Amarelo (LV), were determined the several forms of copper, following a sequential procedure and also the available copper with three extractors commonly used on its evaluation. The contents of copper were determined in fractions: exchangeable (Cu-Troc), organically complexed (Cu-Org), binded to manganese oxides (Cu-OMn), in amorphous (Cu-OFeA) and crystalline (Cu-OFeC) iron oxides; and the content of residual (Cu-Res) was estimated substracting the determinated sorts from the total content (Cu-Total). For the available copper determination, the Mehlich-1 (Cu-Mehlich), EDTA (Cu-EDTA) and DTPA (Cu-DTPA) extractors were used. The content in Cu-Troc fraction varied from traces to 0,3 mg/kg; in Cu-Org from 0,2 to 2,4 mg/kg; in Cu-OMn from 0,1 to 1,1 mg/kg; in Cu-OFeA from 0,6 to 7,4 mg/kg; in Cu-OFeC from 0,4 to 6,8 mg/kg; in Cu-Res from 0,9 to 65,1 mg/kg; and Cu-Total from 3,8 to 75,0 mg/kg. The content of available copper in the soils varied from 0,06 to 1,66 mg/kg in Mehlich-1 extractor; from 0,10 to 1,72 mg/kg in EDTA and from 0,14 to 2,65 mg/kg in DTPA. In relation to the distribution along the profile, the Cu-Troc and Cu-Org showed higher contents in the superficial horizons, while the Cu-OMn tended to increase its contents with the depth. The fractions Cu-OFeA, Cu-OFeC, Cu-Res, the Cu-Total and the available sorts (Cu-Mehlich, Cu-EDTA, Cu-DTPA) did not have a specific distribution along the profile. The soils showed in relation to the rnedium content of Cu-Total, the following order: AQd < PV < LV < PE < Ae < Ce. Among the available copper extractors, the DTPA was the one that solubilized higher quantities, followed by the Mehlich-1 and EDTA. The extractors showed positive and quite significative correlations with Cu-OFeA and Cu-OFeC fractions. In the AQd, PV, LV and PE soils there was the lowest contents of available copper and showed the lowest content of Cu-Total indicating a considerable possibility to its deficiency for crops in these soils.